Meningkatkan Hasil Belajar Ipa Melalui Model Pembelajaran Problem Solving Pada Siswa Kelas 7b SMP Negeri 2 Pandeglang Semester Genap Tahun Pelajaran 2018/2019 - Siti Diah Fatonah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
The low learning achievement at SMP Negeri 2 Pandeglang Class 7B in learning science material on the Interaction of Living Things with their Environment is one proof that learning in accordance with competency standards has not been carried out optimally. One of the causes of the low learning achievement of science at SMP Negeri 2 Pandeglang Negeri 2 Pandeglang Class 7B is possible because the teacher has not utilized all the existing potential and the possibility that the teacher himself has not been able to provide science learning materials about the interaction of living beings with their environment. This research is a classroom action research conducted in two cycles. The results of research and improvement of learning can be seen that students who complete and meet the KKM in the pre-cycle are 55% and 45% are not complete. While in the first cycle, 65% of students who complete and 35% of students who do not complete, meaning that in the first cycle of learning they still do not meet the predetermined KKM, which is an average of 75. As for the learning in the second cycle, it can be seen that the number of students who meet the criteria has been The KKM is 100% and the number of students who do not complete is 0%, so that the science learning process on the subject matter of Interaction of Living Things with the Environment through the Problem Solving learning model for Class 7B students of SMP Negeri 2 Pandeglang Even Semester 2018/2019 Academic Year has been successful and the process learning is stopped